2020
DOI: 10.3390/ijerph17030989
|View full text |Cite
|
Sign up to set email alerts
|

Medication Use among Pregnant Women from the 2015 Pelotas (Brazil) Birth Cohort Study

Abstract: Background: Medication use during pregnancy is a common practice that has been increasing in recent years. The aim of this study is to describe medication use among pregnant women from the 2015 Pelotas (Brazil) Birth Cohort Study. Methods: This paper relies on a population-based cohort study including 4270 women. Participants completed a questionnaire about the antenatal period, including information about medication use. We performed descriptive analyses of the sample and the medications used and adjusted ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 40 publications
(55 reference statements)
1
29
1
1
Order By: Relevance
“…Furthermore, the average number of medications used anytime in pregnancy increased two-fold during that period 2 . More recent research from different countries has found that medications are widely used during pregnancy, with the prevalence of using at least one drug ranging from 60 to 90 percent, excluding vitamins and minerals [3][4][5] .…”
Section: All Authors Declare No Conflict Of Interestmentioning
confidence: 99%
“…Furthermore, the average number of medications used anytime in pregnancy increased two-fold during that period 2 . More recent research from different countries has found that medications are widely used during pregnancy, with the prevalence of using at least one drug ranging from 60 to 90 percent, excluding vitamins and minerals [3][4][5] .…”
Section: All Authors Declare No Conflict Of Interestmentioning
confidence: 99%
“…Numerous studies have examined the patterns of use of prescription and over-the-counter (OTC) medications during pregnancy [ 23 , 24 , 25 , 26 , 27 ]. However, no prior research has aimed to understand the patterns of use of cardiovascular drugs and other therapies for HDP, primarily for those living in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…Such study is highly justified since some patients are believed to make deliberate decisions regarding their medication use, based on their beliefs about the disease and its treatment. [ 29 30 ] Effective counselling has been associated with better and positive outcomes in terms of knowledge and practice of the safe and utilization of drugs and the understanding of many medical conditions that may happen during pregnancy.…”
Section: Introductionmentioning
confidence: 99%